Preserving story choreographies across multiple platforms: an approach to platform-independent reuse of characters' behaviors for games, simulations, animations and interactive videos - Lacet, Demetrius (2020)
This article presents an approach that allows the reuse of choreographies of digital stories, regardless of the platform for which they have been developed. Nowadays, story choreographies are linked to either game technology, simulations or interactive animations for which they have been implemented, so they become unavailable as these platforms become obsolete. This limits their reuse, because to perpetuate these digital stories requires new and repeated efforts and investments in its re-creation for new technological platforms that appear in substitution of the previous ones. We propose a methodology to safeguard the semantics of this "narrative choreographies" in an independent way, allowing them to be automatically adapted to new technological platforms when the original ones become obsolete.